Sex-Specific Social Behavior and Amygdala Proteomic Deficits in Foxp2+/− Mutant Mice - Herrero, Maria Jesus; Wang, Li; Hernandez-Pineda, David; Banerjee, Payal; Matos, Heidi Y.; Goodrich, Meredith; Panigrahi, Aswini; Smith, Nathan Anthony; Corbin, Joshua G. (Frontiers in Behavioral Neuroscience, 2021)
In humans, mutations in the transcription factor encoding gene, FOXP2, are associated with language and Autism Spectrum Disorders (ASD), the latter characterized by deficits in social interactions. However, little is known regarding the function of Foxp2 in male or female social behavior. Our previous studies in mice revealed high expression of Foxp2 within the medial subnucleus of the amygdala (MeA), a limbic brain region highly implicated in innate social behaviors such as mating, aggression, and parental care. Here, using a comprehensive panel of behavioral tests in male and female Foxp2+/– heterozygous mice, we investigated the role Foxp2 plays in MeA-linked innate social behaviors. We reveal significant deficits in olfactory processing, social interaction, mating, aggressive, and parental behaviors. Interestingly, some of these deficits are displayed in a sex-specific manner. To examine the consequences of Foxp2 loss of function specifically in the MeA, we conducted a proteomic analysis of microdissected MeA tissue. This analyses revealed putative sex differences expression of a host of proteins implicated in neuronal communication, connectivity, and dopamine signaling. Consistent with this, we discovered that MeA Foxp2-lineage cells were responsive to dopamine with differences between males and females. Thus, our findings reveal a central and sex-specific role for Foxp2 in social behavior and MeA function.